Roe v. Wade : abortion and the Supreme Court - Romaine, Deborah S., 1956- (San Diego, CA : Lucent Books, 1998)
Discusses the Roe v. Wade ruling which many feel is one of the most controversial decision the Supreme Court has ever rendered.
Includes bibliographical references (pages 102-106) and index.
Keywords: Roe, Jane, -- 1947-2017 -- Trials, litigation, etc. -- Juvenile literature; Wade, Henry -- Trials, litigation, etc. -- Juvenile literature; Roe, Jane, -- 1947-2017 -- Trials, litigation, etc; Wade, Henry -- Trials, litigation, etc; Trials (Abortion) -- Washington, (D.C.) -- Juvenile literature; Abortion -- Law and legislation -- United States -- Juvenile literature; Trials (Abortion); Abortion -- Law and legislation